The Genetic Population Structure of Robinson Crusoe Island, Chile - Mountford, Hayley S.; Villanueva, Pía; Fernández, María Angélica; Jara, Lilian; De Barbieri, Zulema; Carvajal-Carmona, Luis G.; Cazier, Jean-Baptiste; Newbury, Dianne F. (Frontiers in Genetics, 2020)
Studies examining genetic conditions common in Latin America are highly underrepresented in the scientific literature. Understanding of the population structure is limited, particularly Chile, in part due to the lack of available population specific data. An important first-step in elucidating disease mechanisms in Latin America countries is to understand the genetic structure of isolated populations. Robinson Crusoe Island (RCI) is a small land mass off the coast of Chile. The current population of over 900 inhabitants are primarily descended from a small number of founders who colonized the island in the late 1800’s. Extensive genealogical records can trace the ancestry of almost the entire population. We perform a comprehensive genetic analysis to investigate the ancestry of the island population, examining ancestral mitochondrial and Y chromosome haplogroups, as well as autosomal admixture. Mitochondrial and Y chromosome haplogroups indicated a substantial European genetic contribution to the current RCI population. Analysis of the mitochondrial haplogroups found in the present-day population revealed a 79.1% of islanders carried European haplogroups, compared to 60.0% of the mainland Chilean controls from Santiago. Both groups showed a substantially lower contribution of indigenous haplogroups than expected. Analysis of the Y chromosome haplogroups also showed predominantly European haplogroups detected in 92.3% of male islanders and 86.7% of mainland Chilean controls. Using the near-complete genealogical data collected from the RCI population, we successfully inferred the ancestral haplogroups of 16/23 founder individuals, revealing genetic ancestry from Northern and Southern Europe. As mitochondrial and Y investigations only provide information for direct maternal and paternal lineages, we expanded this to investigate genetic admixture using the autosomes. Admixture analysis identified substantial indigenous genetic admixture in the RCI population (46.9%), higher than that found in the Santiago mainland Chilean controls (43.4%), but lower than a more representative Chilepopulation (Chile_GRU) (49.1%). Our study revealed the Robinson Crusoe Island population show a substantial genetic contribution for indigenous Chileans, similar to the level reported in mainland Chileans. However, direct maternal and paternal haplogroup analysis revealed strong European genetic contributions consistent with the history of the Island.